Texts with metadiscourse features are more engaging: a fact or a myth? - Hooi, Chee Mei; Tan, Helen; Lee, Geok Imm; Sharon Sharmini Victor Danarajan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Metadiscourse is a pragmatic linguistic device that writers use to engage with their readers. For decades, research on metadiscourse has mostly centred on academic texts. There were also attempts to examine its use in editorials. However, in this study, attempts are made to investigate the readers’ responses on the use and non-use of metadiscourse in online business news. To gain insights on this objective, thirty participants from a local public university in Malaysia participated in the study. The findings showed that most of the participants preferred to read news with textual metadiscourse because it was clearer, while 16.67% of the participants preferred to read news without textual metadiscourse. The findings also revealed that 93.33% of the participants preferred to read news with interpersonal metadiscourse because it was more engaging, while only 6.67% of the participants preferred to read news without interpersonal metadiscourse. The findings revealed the importance of metadiscourse in business news writings, and as such, texts constructed with and without the presence of metadiscourse could be useful teaching resources for writing instructors in English for Specific Purposes (ESP) writing classrooms.